2022
DOI: 10.33899/ijvs.2021.129435.1647
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in kidney and pancreas induced by energy drinks in adult male rats

Abstract: The study aims to assess the impact of various doses of red bull on kidney and pancreas of male albino rats. Thirty male albino rats were assigned to three groups (10 animals/ group). Control group 1 received standard diet and water, group 2 and group 3 received daily oral doses of 10 ml/kg/rat and 20 ml/kg/rat of the energy drink (red bull) respectively for 30 days. Under light microscope no tissue changes were seen in kidney and pancreas of control group. In group 2 red bull causes vacuolar degeneration as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In addition, energy drinks were shown to cause an imbalance in the pancreatic antioxidants in albino rats. Qassim et al 15 further supported this claim in his study exploring the effect of Red Bull in rats. Rats exposed to the energy drink were noted to have necrosis with mononuclear and degenerative changes of the Islets of Langerhans cells.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, energy drinks were shown to cause an imbalance in the pancreatic antioxidants in albino rats. Qassim et al 15 further supported this claim in his study exploring the effect of Red Bull in rats. Rats exposed to the energy drink were noted to have necrosis with mononuclear and degenerative changes of the Islets of Langerhans cells.…”
Section: Discussionmentioning
confidence: 80%
“…Rats exposed to the energy drink were noted to have necrosis with mononuclear and degenerative changes of the Islets of Langerhans cells. 15 Another study by Haroun et al 16 demonstrated significant distortion of the pancreatic acinar and islet cytoarchitecture in rats ingested with energy drinks. These studies depict an underlying biological relationship between energy drinks and acute pancreatitis and further suggest an alteration of the pancreatic tissue upon exposure to energy drinks.…”
Section: Discussionmentioning
confidence: 98%
“…Consuming caffeinated and sugary EDs encourages insulin resistance resulting in blood sugar levels may increase risk of cardiovascular diseases, obesity and diabetes. 14 The present study mainly focuses on determining the histo-morphometric effects of ED consumption in different doses on the pancreatic tissue of Wistar Albino rats. In this study, the pre and post-experimental body weights of all three group rats were measured.…”
Section: Eds Consumption Results In Different Hazardousmentioning
confidence: 99%
“…Heart sections in rat treated with 10 and 20 mg/kg DMH shows edema, Zenker's necrosis, discontinuation of muscle fibers with foci of infiltration of inflammatory cells and hemorrhage but more sever lesions in dose 20 mg/kg some studies indicated that there are a vasoconstriction occur in the coronary vessels of heart after Acute exposure to DMH (20), heart lesions occurs because of toxic effect of DMH and free radicle that release whereas DMH needs bio activations to induce its mutagenic effects and induce its hepatotoxic effects so its activated metabolically in liver by several steps of reactions to carcinogenic and toxic metabolite through intermediates methylazoxymethanol and azoxymethane and these metabolite affect cardiac muscles and cause cardiomyopathies (18,36,37).because of DMH is a potent colonic and hepatic carcinogen many tumors that occur in colon cause release of H2O2 which is under go detoxification in liver and distributed in all tissues by circulation including heart and many generations of H2O2 are produced from this tumors thus induce cardiomyopathies and continuous injury to rat tissues (38,39). Kidneys sections in rats treated with10 and 20 mg/kg DMH for 8 weeks reveals vacuolar degeneration of epithelial lining renal tubules with cloudy swelling and hyaline casts in some lumen of renal tubules because of application of hydrazine derivates is nephrotoxic and leads to an impairment in renal tubules, decreasing glomerular filtration rate and function (11,40,41), a numbers of animals studies on hydrazine and it derivatives are hypothesized that toxicity is exerted by interfering in urea cycle this occurred by increased levels Nα-acetyl citrulline and arginosuccinate (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%